Globamericanización educativa y tecnocracia: la economía y la administración de Estados Unidos en México y América Latina - Lorusso, Fabrizio (Confluenze. Rivista di Studi Iberoamericani, 2017)
This article analyzes historically the process of Americanization of economic science and management, especially in Mexico and Latin American, and, in the framework of accelerated globalization processes, the gradual homologation of these disciplines to US models that matures through the 20th century and culminates in the 1980s. The concept of educative Globamericanization refers to a “U.S. led globalization” of economics and management that marks the political rise of technocrats and money doctors, the persistence of elites and the success of Americanized postgraduate courses such as the MBA.